The Effectiveness of Implementing Premarital Hearings as a Preventive Model for Strengthening Family Resilience among Members of the Indonesian National Police from the Perspective of Maqāṣid al-Sharī’ah - Asev Kurniawan; Muhammad Rusjana; Dwi Putri Melati; Muhammad Havez (Universitas Islam Negeri Raden Intan Lampung, 2026)
The increasing divorce rate among members of the Indonesian National Police indicates that compliance with marriage procedures has not fully strengthened family resilience. This study aims to analyze the implementation of premarital hearings within the Mobile Brigade Corps of the Lampung Regional Police, examine their conformity with Islamic law, and evaluate their effectiveness as a preventive model for strengthening family resilience. This research employed an empirical juridical approach using qualitative methods through observation, in-depth interviews, documentation, and normative analysis based on Asy-Shatibi's Maqāṣid al-Sharī’ah perspective. The findings reveal that premarital hearings function as an institutional development instrument integrating spiritual, psychological, organizational, and professional ethical dimensions, thereby serving not only administrative requirements but also enhancing couples' preparedness for the demands of police service. This study proposes the Integrated Organizational Premarital Development Model as its conceptual novelty. Strengthening the curriculum, improving facilitator competence, and providing post-marital assistance are recommended to enhance the sustainability and effectiveness of the program.